Costal Cartilage Calcification in a Caucasian Population: Machine Learning Recommendations for Chest CT-guided Rhinoplasty Planning - van Dam, Victor S.; Berzenji, Diako; van den Berg, Aaike S.; van Zijl, Floris V. W. J.; Nagtegaal, Andries P.; Kremer, Bernd; Datema, Frank R. (Facial Plastic Surgery, 2025)
Autologous costal cartilage calcification (CCC) can impact the course and long-term results of rhinoplasty. Preoperative information about the presence, severity, and pattern of CCC helps to assess donor site suitability and rhinoplasty planning.To use machine learning to identify a sex-specific age threshold beyond which a preoperative chest CT is likely to reveal CCC relevant for rhinoplasty planning.Cross-sectional retrospective study of 662 Caucasian adults.Prevalence, severity, and patterns of CCC in ribs five to eight were assessed by three independent reviewers. A machine learning algorithm was used to predict the age threshold beyond which a chest CT scan is beneficial to rhinoplasty planning.The prevalence of CCC in Caucasian adults was 89.6%. Nearly all individuals over the age of 50 exhibited some form of CCC. In young females CCC was more severe and prevalent in the central core of ribs five to eight compared with age-matched males.A chest CT is recommended in females over 23 years and males over 40 years. No data-driven recommendations regarding an upper age limit for costal cartilage use could be determined from the data.
Keywords: machine learning; costal cartilage calcification; Caucasian; rhinoplasty